Redistribution of power flow in complicated closed overhead networks 10 kv for reduce loss and improving the quality of electricity - V. T. Sidorova; V. V. Karchin (Известия высших учебных заведений: Проблемы энергетики)
The distribution networks of the most widespread network loop circuit - closed network, open at one of its nodes. This disconnection point must be selected according to the criterion of minimization the active power losses, electric power and ensure the reliability of power supply. Definition of a rational point for breaking the overhead network, corresponding to the minimum active power losses, is quite a tedious task. In practice, therefore, this point is taken randomly, which leads to considerable losses of active power and voltage. Currently, there are no methods for determining the point of breaking for meshed networks of 10 kV overhead, taking into account the power loss in the lines and the actual value of the voltage, which results in an incorrect definition of the point of rupture. The method of determining the optimum point of breaking meshed network of 10 kV is developed. It is ensuring minimal loss of active power. The validity of the proposed method was checked by the example of several typical 10 kV networks.